2004
DOI: 10.1093/hsw/29.2.137
|View full text |Cite
|
Sign up to set email alerts
|

The Impact, Meaning, and Challenges of Work: Perspectives of Individuals with HIV/AIDS

Abstract: This study used a qualitative methodology to examine the work needs and experiences of 29 individuals with HIV/AIDS. Findings revealed the value and significance of employment, concerns related to social security benefits and discrimination, informal and formal supports and barriers, and the needs of unemployed compared with employed individuals. Implications consider the best methods of helping individuals with HIV/AIDS obtain or maintain employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…Despite the fact that seropositive mothers' employment status did not differ by their object (CD4 t-cell count), social support (receipt of advice or support from church pastor and the need to have borrowed money from family members or friends to help pay for over-the-counter products-nutritional drinks, vitamins, or minerals), or energies (annual income) resources (Table not shown but available on request), the mean perceived stress score of 13.71 for employed seropositive mothers was lower than that of 20.85 for seropositive mothers who were unemployed (t = −2.51, p = .01). The fact that HIV/AIDS-infected mothers did not differ by employment status with respect to these aforementioned resources help to support the assertion that the intrinsive benefits that are derived from employment, such as a sense of self-fulfillment and self-esteem building, are vital to the psychological well-being of seropositive mothers and, therefore, serve as a buffer against stress (Timmons & Fesko, 2004).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Despite the fact that seropositive mothers' employment status did not differ by their object (CD4 t-cell count), social support (receipt of advice or support from church pastor and the need to have borrowed money from family members or friends to help pay for over-the-counter products-nutritional drinks, vitamins, or minerals), or energies (annual income) resources (Table not shown but available on request), the mean perceived stress score of 13.71 for employed seropositive mothers was lower than that of 20.85 for seropositive mothers who were unemployed (t = −2.51, p = .01). The fact that HIV/AIDS-infected mothers did not differ by employment status with respect to these aforementioned resources help to support the assertion that the intrinsive benefits that are derived from employment, such as a sense of self-fulfillment and self-esteem building, are vital to the psychological well-being of seropositive mothers and, therefore, serve as a buffer against stress (Timmons & Fesko, 2004).…”
Section: Discussionmentioning
confidence: 70%
“…In a sample of 757 unemployed seropositive persons, Brooks et al (2004) found nearly three-quarters (74%) to report that they plan to work either now or in the near the future. Findings from Timmons and Fesko's (2004) focus group interviews with 29 people living with the HIV/AIDS disease help to validate the high value that is placed on employment. These seropositive persons expressed a strong desire to work for not only the economic benefits but also for a sense of self-respect and self-fulfillment.…”
Section: Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PWHIV may require ongoing medical care and monitoring, which are usually provided by specialists and are generally only accessible in large urban centers. Such geographic restrictions on job mobility can affect employability and opportunities for advancement (Timmons & Fesko, 2004). As supported by existing research, it is obvious that today's economic dynamics can complicate PWHIV's reentry into the job market.…”
Section: The Vocational Task In the Context Of Adaptation To Hiv/aidsmentioning
confidence: 98%
“…Findings from Timmons and Fesko's [26] focus group with 29 persons with HIV/AIDS underscore the high value that is now placed on employment for persons with HIV/AIDS. These patients expressed a strong desire to work not only for the economic benefits that employment provides but also for a sense of self-respect and self-fulfillment.…”
Section: Physical-social Environment Factors: Physical Stamina and Womentioning
confidence: 99%